The Complete Retirement Handbook : The Most Authoritative Guide Available - Bowman, Forest J. (Book collections on Project MUSE., 1989)
If you are 20 or 30 years of age and just starting out in a career, this book can serve you as an excellent road map for your future retirement. If you are 40 to 50 years of age, this book can become the life-saver that can make your shortly-to-come retirement more full. If you are over 50 years of age, you need to rush out and get this book to keep from suffocating during your impending retirement. In other words, this book is an excellent volume for anyone who is in the American work force.